Environmental Cleanliness: Village Government Program In Indonesia - Fitriani Nasihah; Imam Tabroni (IHSA Institute, 2023)
Problems about environment life Becomes problem urgent because still many case environment life which not yet can handled in a manner right, including problems related to waste and clean water. It is also that occurred in Salem Village, where the problem of garbage and clean water is still not yet resolved managed properly due to the absence of clear management though the government's role is needed in dealing with this. This research aim for know role government Village in resolve problem waste and clean water in Salem Village. This study uses an approach qualitative descriptive. Data collection techniques through interviews, observation, and documentation. The informants who were asked for data were the Head of Salem Village, the Chair and Secretary Board of Directors, and 30 inhabitant Village Salem. Test validity data use technique triangulation and source triangulation. The research results show that role government Village in resolve problem rubbish and water clean that is by performing services, outreach, empowerment, making rules, and development regarding waste and clean water.